If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + 11 + 6x + 6 = 136 Reorder the terms: 11 + 6 + 11x + 6x = 136 Combine like terms: 11 + 6 = 17 17 + 11x + 6x = 136 Combine like terms: 11x + 6x = 17x 17 + 17x = 136 Solving 17 + 17x = 136 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-17' to each side of the equation. 17 + -17 + 17x = 136 + -17 Combine like terms: 17 + -17 = 0 0 + 17x = 136 + -17 17x = 136 + -17 Combine like terms: 136 + -17 = 119 17x = 119 Divide each side by '17'. x = 7 Simplifying x = 7
| x+5/x-7=x-2/x | | x+5+22=4x-9 | | 3a+4ab=9a | | p=v2/r | | 3k^2-5k+1=0 | | 4+7(7p+5)=39 | | 3a+4ab= | | 68x+2+28=82x+1 | | -4(5t-3)+5t=4t-9 | | [40+10r]=27-3r | | 32-x/5=x/3 | | 3/8x+7/8=-1 | | 2x-8+5=0 | | z/3=21 | | 2s+7=3-s | | 1/5(20x+30)=1/3(6x+36) | | 5[2r+8]=27-3r | | 4(4a-2b+5)+2(2a-5)=e | | 5x+2+154=45x-4 | | 32/4*3+14*10 | | 39-3s=23(2s-3) | | 6a^2-11a-2= | | 1/2x-2/5=0 | | 4p-61=-17 | | 1/5(4-3x) | | 6g+5-3g=12-7g+9 | | x/3-15 | | -5(6y-4)-y=-2(y-4) | | 27a^2x^2+45a^2x+36a^2=0 | | -9=r+(-15) | | 10x-4+30=14x+2 | | 9x^2-86x+45= |